Analysis of motives and patient satisfaction in oncological second opinions provided by a certified university breast and gynecological cancer center - Löhberg, Christian; Meyer, Julia; Häberle, Lothar; Hack, Carolin; Jud, Sebastian; Hein, Alexander; Wunderle, Marius; Emons, Julius; Gaß, Paul; Fasching, Peter; Egloffstein, Sainab; Krebs, Jessica; et al. (Archives of Gynecology and Obstetrics, 2020)
Purpose: Second opinions in oncology are becoming increasingly important in an era of more complex treatments and a growing demand for information by patients. Therefore, we analyzed their effects and influencing factors like patients’ motives, subjective extent of information and satisfaction with communications. Methods: This prospective study evaluated second opinions for patients with breast cancer or gynecological malignancy. The patients received a questionnaire before and two months after, which inquired expectations, reasons, and satisfaction with the second opinion and the attending physicians. Results: A total of 164 patients were included and the majority had breast cancer (75.0%). Receiving the second opinion made 89.7% feel better informed, their need for information decreased (from 75.3% to 39.2%, P < 0.0001), and satisfaction with doctor–patient communications increased (from 61.9 to 91.8%, P = 0.0002). There were various reasons for requesting a second opinion, e.g., the extremely stressful situation of a cancer diagnosis, hope for change in the treatment recommendation or dissatisfaction with the initial physicians. Conclusions: Second opinions can lead to significantly greater patient satisfaction, meeting the need for information and leading to better management of patients in the extremely stressful situation of a cancer diagnosis. Doctor–patient communications play a key role.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Breast cancer; Doctor–patient communication; Gynecological malignancy; Oncology center; Patient satisfaction; Second opinion